President Jimmy Carter at Fresno Air Terminal Rally - Watkins, Howard K. (1977)
Assembly Member Rick Lehman, State Senator George Zenovich, Governor Jerry Brown, Congressman Bernie Sisk, President Jimmy Carter, Mayor Daniel Whitehurst, Senator Alan Cranston, ?